The Management of Negotiation Process on the Animal Welfare Dispute in the Bandung Zoo - Herlina Agustin; Rinda Aunillah Sirait; Dandi Supriadi (Ikatan Sarjana Komunikasi Indonesia, 2018)
Management of conflict and negotiation played an important role in solving a dispute. Both actions were not simple tasks in resolving conflicts since different points of view usually involve. This was what happened in the dispute of animal welfare issue between Bandung Zoo and Scorpion Wildlife Foundation. The dispute that became the focus of this article related to the accusation raised by the Scorpion Wildlife Foundation towards the Bandung Zoo in terms of animal welfare abandonment. The conflict between the two organizations has increased because the zoo did not accept the allegations and intended to bring the foundation to a legal court for the reason of defamation. This article looked at the use of the management of conflict and the negotiation to resolve this conflict by the Agency of Natural Resources of West Java as facilitator. The study used constructive case study method to chronologically construct the conflict and the use of negotiation. The results showed that the facilitator dominated the negotiation process, while the conflicting parties have not had any agreement to resolve the problem. The condition had a potential to be invalid any time if the dispute was not completely resolved.